Assessment of Genetic Divergence in Rice (Oryza sativa L.) Germplasm Using D2 Analysis - Vinayak V. Thakare; G. M. Lal; Bineeta M. Bara (Archives of Current Research International, 2025)
The present investigation was conducted with 41 genotypes of Rice during Kharif 2023 under Randomized Block Design (RBD) with three replications. Data were recorded for thirteen quantitative characters to obtain estimates of variability, heritability, genetic advance and genetic divergence. Significant differences were observed among the genotypes for all the characters studied. This study concluded, the highest grain yield was observed in VASUMATHI 38.9 followed by DHAN-69 34.33 based on mean performance at Prayagraj region. A higher magnitude of PCV as well as GCV coefficient of variation was noted for the number of total tillers per plant (22.05) and (21.20). Whereas the lowest PCV and GCV coefficient of variation was recorded for Days to maturity (7.40 and 6.80). High estimates of heritability (above 60%) in broad sense were recorded for all the thirteen characters under study, which ranged from 92.45% number of total tillers per plant to 61.55 harvest index. along with high genetic advance for number of spikelets per panicle (54.38), plant height (cm) (27.95), days to 50% flowering (22.93), and days to maturity (17.72). Biological yield (g) (15.33), harvest index (%) (11.06) and flag leaf length (cm) (10.05) D2 analysis distributed the 41 genotypes into six clusters. The largest cluster was cluster I with 36 genotypes followed by cluster II, III, IV, V, VI with 1 genotype each. Highest contribution in manifestation of genetic divergence was exhibited by grain yield per plant (22.82) followed by biological yield (21.28) and test weight (12.56). Lowest intercluster distance was between cluster I and cluster IV which was (60.58). The intercluster distance was maximum between cluster IV and VI (247.17). Therefore, genotypes present in these clusters should be used for the future hybridization program. Highlights: Germplasms were grouped into 6 clusters. Cluster IV and VI were the most divergent clusters